2014
DOI: 10.1134/s0023158414050140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the composition and structural and size characteristics of composites based on stabilized zirconia and transition metal (Cu, Co, Ni) oxides on their catalytic properties in methane oxidation reactions

Abstract: The effects of transition metal (Cu, Co, Ni) oxides and platinum group metals (Pt, Pd, Rh) in composites based on Y(Sc) stabilized zirconia on their catalytic properties (activity, selectivity, sulfur resis tance) and service life characteristics (thermal stability, performance stability) in methane oxidation reactions have been investigated. The high activity of the composites (75-99% methane conversion at 600-800°C) correlates with the amount and mobility of surface oxygen in these materials. The promoting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In a catalytic study, Co-Cu/YSZ+CeO 2 with a 50:50 mix of Co and Cu produced by impregnation into YSZ showed very little carbon deposition after exposure to a 2:1 CH 4 :O 2 mixture for 20 h at 800 °C, much lower than a comparative Ni-Cu sample . A similar study conducted with dry butane found that the amount of carbon deposition increased with increasing metal loading, indicating that the metal is still encouraging the formation of carbon, despite the lack of nickel .…”
Section: Materials Design Strategies For Carbon Tolerance In Sofc Anodesmentioning
confidence: 93%
See 2 more Smart Citations
“…In a catalytic study, Co-Cu/YSZ+CeO 2 with a 50:50 mix of Co and Cu produced by impregnation into YSZ showed very little carbon deposition after exposure to a 2:1 CH 4 :O 2 mixture for 20 h at 800 °C, much lower than a comparative Ni-Cu sample . A similar study conducted with dry butane found that the amount of carbon deposition increased with increasing metal loading, indicating that the metal is still encouraging the formation of carbon, despite the lack of nickel .…”
Section: Materials Design Strategies For Carbon Tolerance In Sofc Anodesmentioning
confidence: 93%
“…Cell tests on the 4:1 Cu:Ni anode showed a large increase in performance caused by carbon deposition improving electronic percolation. A catalytic study of Ni-Cu/YSZ+CeO 2 with the Ni, Cu, and CeO 2 impregnated into the YSZ also found significant carbon deposition in the 50:50 Ni:Cu sample after exposure to a 2:1 CH 4 :O 2 mixture at 800 °C for 20 h. 151 The amount of carbon was also not reduced by addition of Pd to the composite. A sample with a 25:75 Ni:Cu mixture in contrast showed no carbon deposition.…”
Section: Alloying or Replacement Of Nickel With Base Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant efforts have been made to enhance carbon deposition resistance of Ni-cermet anodes. One class of strategy is to alloy Ni with other metals. The high cost of noble metals basically rules out wide applications of Ni-noble metal alloys. While Ni alloying with top row transition metals may improve their carbon deposition resistance, the corresponding catalytic activities are usually sacrificed.…”
Section: Introductionmentioning
confidence: 99%
“…Present efforts are directed towards developing anode materials capable of operating with hydrocarbon fuels without carbon deposition [2][3][4]. As different types of anodes have their own advantages, it is important to compare the anodes for the type of fuel and application under consideration Following our previous work on gasifier SOFC gas turbine systems development [1,[5][6][7][8][9][10], in this study we compare the performance of different anode materials when fed with H 2 , CO and syngas.…”
Section: Introductionmentioning
confidence: 99%